Loss of Pde6a Induces Rod Outer Segment Shrinkage and Visual Alterations in pde6aQ70X Mutant Zebrafish, a Relevant Model of Retinal Dystrophy - Crouzier, Lucie; Diez, Camille; Richard, Elodie M.; Cubedo, Nicolas; Barbereau, Clément; Rossel, Mireille; Delaunay, Thomas; Maurice, Tangui; Delprat, Benjamin (Frontiers in Cell and Developmental Biology, 2021)
Retinitis pigmentosa (RP) is one of the most common forms of inherited retinal degeneration with 1/4000 people being affected. The vision alteration primarily begins with rod photoreceptor degeneration, then the degenerative process continues with cone photoreceptor death. Variants in 71 genes have been linked to RP. One of these genes, PDE6a is responsible for RP43. To date no treatment is available and patients suffer from pronounced visual impairment in early childhood. We used the novel zebrafish pde6aQ70X mutant, generated by N-ethyl-N-nitrosourea at the European Zebrafish Resource Centre, to better understand how PDE6a loss of function leads to photoreceptor alteration. Interestingly, zebrafish pde6aQ70X mutants exhibited impaired visual function at 5 dpf as evidenced by the decrease in their visual motor response compared to pde6aWT larvae. This impaired visual function progressed with time and was more severe at 21 dpf. These modifications were associated with an alteration of rod outer segment length at 5 dpf and 21 dpf and cone loss at 21 dpf. The cone loss was due to increased apoptosis, visualized by active caspase-3 immunostaining. In summary, these findings suggest that rod outer segment shrinkage due to Pde6a deficiency begins very early in zebrafish, progresses with time and is associated with cone loss at older age. The zebrafish pde6aQ70X mutant represents an ideal model of RP to screen relevant active small molecules that will block the progression of the disease.